Children's Literature, Carrie Hintz (2019). Issue 1 (1st August 2021) - Hillel, Margot
Review of: Children's Literature, Carrie Hintz (2019)Abingdon, Oxford and New York: Routledge, 188 pp., ISBN 978-1-13866-794-5, h/bk, 143.20ISBN 978-1-13866-795-2, p/bk, 29.99ISBN 978-1-31561-883-8, e-book, 21.59